Sunday morning live ; v.1 a collection of drama sketches from Willow Creek Community Church - Pederson, Steve; Willow Creek Community Church (Grand Rapids, MI Zondervan, 1992)
A collection of contemporary drama sketches which raise Biblical questions. Contents : v.1.
Keywords: Christian drama